Estudo das propriedades estruturais, térmicas, ópticas e espectroscópicas do vidro cálcio-boroaluminato dopado com Sm2O3 - BRITO, Diogo Ramon do Nascimento (2016)
The calcium boroaluminate (CaBAl) glass is an important class of optical materials for diverse applications, among them the use as active media for solid state lasers. CaBAl glasses are chemically stable, present easy glass formation, show excellent mechanical and thermal properties, have a good transparency and wide range of transparency at wavelengths from visible to near infrared. Among the trivalent RE ions, Sm3+ ion is one of the widely used ions with applications in high-density optical storage, under sea communication and color display. Its emitting level 4G5/2 exhibits relatively high quantum efficiency and also shows different quenching emission channels, that can be used in new light sources, fluorescent displays devices, UV-sensor and visible lasers. Samples of CaBAl glass with composition of (25-x)CaO-50B2O3-15Al2O3-10CaF2- xSm2O3, with Samarium concentration varying from 0.5 to 7 wt%, were prepared by using melt-quenching method in air atmosphere. The samples were prepared with different concentrations of Sm2O3, aiming understanding how the dopant changes the structural, thermal, optical and spectroscopic properties. X-ray diffraction results confirm the amorphous nature of these samples. The measured volumetric density showed an increase with Sm2O3 doping. The Raman and FTIR results confirm the structural change of the samples showing the presence of BO3, BO4 and non-bridging oxygens structural unity. The hardness increases with the dopant increasing. From DTA analysis was observed an increase of Tg, Tx values for all samples with the increase of Sm2O3. The refractive index do not vary within the error bar with the increase of Sm2O3. The absorption bands were attributed to Sm3+ transitions from the ground state 6H5/2 to the various excited states. The luminescence spectra present emission bands assigned to the appropriate electronic f-transitions of Sm3+ ions, there are four emission bands at 565, 602, 649 and 710 nm. The maximum intensity of luminescence at room temperature was obtained with 2wt% sample of Sm2O3 and decreasing up this concentration. The luminescence intensity presented a decrease with the increase of the temperature for all studied samples. The experimental lifetime decrease with the increase of Sm2O3. The results point out this glass system as a good candidate to be used in the development of photonics devices.